OUTSORCHING dalam Manajemen Sumber Daya Manusia - amruzziyad; Sahwi, Mohamad Iwan Fitriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study employs a quantitative approach using a survey method through questionnaire distribution to analyze the impact of outsourcing practices in Human Resource Management (HRM) on satisfaction and performance. The data analysis technique used is multiple linear regression. The findings indicate that outsourcing is a strategy used by companies to enhance efficiency, reduce costs, and focus on core activities. Effective implementation requires a systematic process, including needs analysis, careful selection of qualified service providers, clear contract negotiation, and continuous monitoring of service execution. Additionally, compliance with labor regulations and the protection of employee rights are essential considerations. When applied properly, HR outsourcing can deliver significant strategic benefits to organizations.